2010
DOI: 10.1099/ijs.0.008607-0
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic study of Marinomonas strains isolated from the seagrass Posidonia oceanica, with descriptions of Marinomonas balearica sp. nov. and Marinomonas pollencensis sp. nov.

Abstract: Novel aerobic, Gram-negative bacteria with DNA G+C contents below 50 mol% were isolated from the culturable microbiota associated with the Mediterranean seagrass Posidonia oceanica. 16S rRNA gene sequence analyses revealed that they belong to the genus Marinomonas. Strain IVIA-Po-186 is a strain of the species Marinomonas mediterranea, showing 99.77 % 16S rRNA gene sequence similarity with the type strain, MMB-1T, and sharing all phenotypic characteristics studied. This is the first description of this species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 31 publications
4
52
0
Order By: Relevance
“…Marinomonas strain IVIA-Po-185T and M. pontica 46-16 have been isolated from the sea grass Posidonia oceanic . They are helical in shape, have salt tolerance up to 10% and grow at temperatures between 5–37°C and 4–33°C, respectively (Espinosa et al 2010). The halotolerant isolate Marinomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Marinomonas strain IVIA-Po-185T and M. pontica 46-16 have been isolated from the sea grass Posidonia oceanic . They are helical in shape, have salt tolerance up to 10% and grow at temperatures between 5–37°C and 4–33°C, respectively (Espinosa et al 2010). The halotolerant isolate Marinomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar bacteria lineages were also found in epiphytic bacterial communities of seaweeds (Egan et al, 2013) and in the core microbiota of seagrass roots, which appears dominated by Gammaproteobacteria (Egan et al, 2013) represented in our study by three strains affiliated with Marinomonas posidonica, and one strain affiliated with M. mediterranea. Previous studies revealed that microorganisms within the genus Marinomonas can be readily isolated from the different tissues of P. oceanica (Espinosa et al, 2010;Lucas-Elio et al, 2011), including Marinomonas balnearica, pollencensis, mediterranea, and posidonica. Marinomonas posidonica is frequently detected in the microbiota of P. oceanica, and some authors suggest an ancient relationship between these two species (Lucas-Elio et al, 2011), including the bacteria promoting the growth of the angiosperm (Celdran et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The natural inducer may well be L-Lys, since it is the substrate of the enzyme, while the others would act simply because of the striking structural similarity of all these compounds containing a side chain with at least three carbons and an amino group. M. mediterranea is a component of the microbiota associated with the marine plant Posidonia oceanica (12). One possibility is that the presence of L-Lys reflects an environment in close proximity to the plant that would release the amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…The melanogenic marine bacterium Marinomonas mediterranea is a component of the microbiota of the marine plant Posidonia oceanica, which is of great importance in Mediterranean Sea ecosystems (12). It synthesizes an antimicrobial protein that was initially named marinocine and was later named LodA (24,25).…”
mentioning
confidence: 99%